Security Awareness Strategy for Phishing Email Scams: A Case Study One of a Company in Singapore - Febriyani, Widia; Fathia, Dhiya; Widjajarto, Adityas; Lubis, Muharman (JOIV : International Journal on Informatics Visualization, 2023)
Social Engineering Procedures and phishing are some of the standard procedures and problems today, mainly through sophisticated media such as email, the official means of communication companies use. Phishing emails are usually associated with Social Designing. They can be sent via joins and connections in this email, but they are not secure. Proliferation can be hacked into private/confidential data or total control over the computer/Email without the client's knowledge. The method used in this research is a cycle that will run continuously in a life cycle, starting from problem identification, then generating ideas and evaluating the Implementation of solutions. At each stage, a thorough checking process is needed to obtain results. Follow what you want. Achieved. The results of this study provide recommendations and some suggestions that companies can make; this aims to be one of the doors that provides restrictions for access from parties who are not entitled to access the application. Some thought has shown that this attack is growing and affecting the population. The evaluation stages in this study consist of 5 phases. Each phase is a step used to prevent both the system and the behavior in the company. Awareness is critical at the start considering this is the basis for the organization to determine who will take care of the personnel's knowledge related to information security. It thinks about using survey writing strategies and recommendations that can be made in anticipation of an attack, such as setting up representation or attention as early and often as possible.